New morphological information on, and species of placoderm fish Africanaspis (Arthrodira, Placodermi) from the Late Devonian of South Africa - Gess, R.; Trinajstic, Kate (Public Library of Science, 2017)
Here we present a new species of placoderm fish, Africanaspis edmountaini sp. nov., and redescribe Africanaspis doryssa on the basis of new material collected from the type locality of Africanaspis. The new material includes the first head shields of Africanaspis doryssa in addition to soft anatomy for both taxa. Hitherto Africanaspis was entirely described from trunk armour and no record of body and fin outlines had been recorded. In addition the first record of embryonic and juvenile specimens of Africanaspis doryssa is presented and provides a growth series from presumed hatchlings to presumed adults. The presence of a greater number of juveniles compared to adults indicates that the Waterloo Farm fossil site in South Africa represents the first nursery site of arthrodire placoderms known from a cold water environment. The preservation of an ontogenetic series demonstrates that variation within the earlier known sample, initially considered to have resulted from ontogenetic change, instead indicates the presence of a second, less common species Africanaspis edmountaini sp. nov. There is some faunal overlap between the Waterloo Farm fossil site and faunas described from Strud in Belgium and Red Hill, Pennsylvania, in north America, supporting the concept of a more cosmopolitan vertebrate fauna in the Famennian than earlier in the Devonian. © 2017 Gess, Trinajstic. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.